Developing Big Puzzle Learning Media to Enhance Cooperation Skills in Early Childhood - Umaemah Marsuki AR; Kartini Marzuki; Azizah Amal; Muhammad Akil Musi; Herlina Herlina (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
The development of social–emotional competencies, particularly cooperation skills, is a crucial aspect of early childhood education as it supports children’s ability to interact effectively, share responsibilities, and engage in group activities. However, limited use of innovative and engaging learning media often hinders the optimal development of these skills. This study aims to develop Big Puzzle learning media and examine its effectiveness, validity, and practicality in improving the cooperation skills of children aged 5–6 years. This research employed a Research and Development (R&D) approach. Data were collected through interviews, observations, and questionnaires. The findings reveal that the design process of the Big Puzzle learning media includes the development of both the puzzle product and a supporting guidebook. The effectiveness of the media was categorized as very effective, with a score of 3.4. Furthermore, the level of development in enhancing children’s cooperation skills obtained a score of 3.5, indicating an improvement category. In terms of product quality, the Big Puzzle learning media achieved a very valid classification based on expert validation results. Additionally, the practicality level reached a score of 3.4, which falls into the practical and highly practical category for classroom use. These results indicate that the developed Big Puzzle learning media is valid, practical, and effective in enhancing the cooperation skills of children aged 5–6 years. Therefore, this media can be utilized as an alternative learning tool to support the development of social interaction and collaborative abilities in early childhood education.